Effectiveness of Image Media, Songs, and Educational Games in Arabic Language Learning for Elementary School Students - Wijaya, Mualim; Khoiri, Ulfatun Nabila (STUDI ARAB, 2024)
Arabic language learning at MIN 1 Probolinggo adopts an innovative approach that combines vocabulary usage, singing, and educational games to enhance students' understanding. To meet students' needs for Arabic proficiency, the use of visual media such as pictures and flashcards has proven effective in enriching vocabulary and improving learning outcomes. The singing method creates a relaxed and enjoyable learning atmosphere while strengthening memory, pronunciation, and understanding of Arabic culture. The combination of listening, singing, and analyzing song lyrics generates student enthusiasm, making the learning process more engaging. Additionally, educational games serve as motivators, encouraging students to be more active and involved without feeling burdened. With this approach, MIN 1 Probolinggo is committed to continuously developing effective teaching methods to enhance students' overall Arabic language proficiency.